Queering Bioethics: A Queer Bioethical Inventory of Surrogacy - Tiia Sudenkaarne (Elsevier BV, 2022)
Summary
Queer bioethics is a latterly explicated field of bioethics developed by Lance Wahlert and Autumn Fiester, focusing on gender nonconformity and sexual diversity. Queer bioethical inquiries often involve people identifying as lesbian, gay, trans, queer or intersex (= LGBTQI) to name some of the established identity categories of such nonconformity and diversity. Topics of queer bioethical interest can include, for example, issues discussed in mainstream bioethics as gender reassignment or sex affirmation of trans- and intersex people respectively, or reproductive justice for same-sex couples accessing assisted reproduction technology. Further, however, queer bioethics interrogates the basis on which certain socio-medicalized views on gender and sexuality are justified in medical ethics, wishing to critically renegotiate these justifications to allow more human flourishing. This is also a call for dismantling the cis- and heteronormative bioethical foundations of public health. This article offers an introduction to queer bioethics accompanied by the queer bioethics inventory (QBI) formulated by Wahlert and Fiester for bioethical methodology, by focusing on the case of surrogacy in Finland. The case is selected neither because it is the most queer bioethically appalling nor because it is a rare one. On the contrary: the case has nothing explicitly to do with LGBTQI people, and allowing surrogacy as treatment is not globally uncommon. To subject a seemingly non-queer, common bioethical practice, for a queer bioethical analysis reveals the need for queer bioethics.
Résumé
La queer bioethics est un domaine de bioéthique expliquée récemment développé par Lance Wahlert et Autumn Fiester, centré sur la non-conformité entre sexes et la diversité sexuelle. Les enquêtes bioéthiques transgenre impliquent souvent des personnes qui s’identifient comme lesbiennes, gays, trans, transgenre ou intersexué (= LGBTQI) pour nommer certaines des catégories d’identité établies de cette non-conformité et diversité. Les sujets d’intérêt queer bioethics peuvent comprendre, par exemple, les questions abordées dans la bioéthique générale comme la réaffectation des sexes ou l’affirmation du sexe des personnes trans- et intersexuées respectivement, ou l’égalité de reproduction pour les couples de même sexe accédant à la technologie de reproduction. Par ailleurs, la queer bioethics interroge la base sur laquelle certains points de vue sociomédicaux sur le genre et la sexualité sont justifiés dans l’éthique médicale, désireux de renégocier de manière critique ces justifications pour permettre un plus grand épanouissement humain. Il s’agit également de démanteler les fondements bioéthiques cis-et hétéronormatif de la santé publique. Cet article offre une introduction à la queer bioethics accompagnée de l’inventaire de la queer bioethics (QBI) formulé par Wahlert et Fiester pour la méthodologie bioéthique, en se concentrant sur le cas de la maternité de substitution en Finlande. Le cas est choisi ni parce qu’il est le plus transgenre bioéthiquement épouvantable ni parce qu’il est rare. Au contraire : le cas n’a rien explicitement à voir avec les gens LGBTQI, et permettre la maternité de substitution comme traitement est assez courant. Soumettre une pratique bioéthique commune apparemment non-transgenre pour une analyse queer bioethics révèle la nécessité de la queer bioethics.
Previous article in issue